Evaluation of Kurdish grammar and reading books from the perspective of teachers (Second cycle of primary school) as an example - Marouf, Muslim Saber; Hussein, P.D. Shilan Omar (Sulaimani Journal for Humanities, 2026)
· Abstract This study, entitled “Evaluating the Kurdish Grammar and Reading Textbooks from Teachers’ Perspectives: The Second Cycle of Primary Education as a Case Study”, aims to assess the Kurdish grammar and reading textbooks used in the upper primary primary education from teachers’ viewpoints. It also seeks to identify teachers’ suggestions for improving these textbooks. To achieve these aims, a descriptive–analytical research design was employed. The study population comprised all teachers in the centres of Sulaymaniyah Governorate across both the Eastern and Western Education Directorates for the academic year 2024–2025, totalling 815 teachers. The sample consisted of 307 teachers of both genders, selected randomly. The research instrument was a questionnaire including 66 items distributed across eight domains, developed based on relevant literature and previous studies. Data were analysed using the one-sample t-test, independent-samples t-test, ANOVA, Pearson’s correlation coefficient, and Cronbach’s alpha. The study reached the following main conclusions: 1. Overall, the results indicate that, according to the teachers, the upper primary textbooks are at a poor level. 2. From the teachers’ perspective, statistically significant differences were found between male and female students’ average scores, in favor of female students. 3. Finally, teachers proposed many suggestions for improving the textbooks of the second cycle of primary education.
Keywords: Evaluation; Textbook; Teacher Reading; Grammar